The Relationship of Psychological Stress With Breast Milk Production to Breastfeeding Mothers Post Delivery in the Clinic Wulandari Medan in 2021 - Desideria Yosepha Ginting; Layari Tarigan; Dwi Handayani; Lasima Hotma Sitio (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Postpartum mothers are mothers in the postnatal period, postpartum mothers often experience psychological stress which usually occurs in the first week to the sixth week after delivery. Mother's psychological stress usually occurs due to hormonal factors, family support, new roles, busy taking care of babies and lack of knowledge. Breast milk is a very important source of nutrition to meet the needs of babies, one of the factors that affect breast milk production is psychological stress. The purpose of this study was to identify the relationship between psychological stress and breast milk production in postpartum breastfeeding mothers at the Wulandari Clinic, Medan. This type of research is quantitative research with a correlation research design with a cross-sectional approach. The sampling technique in this study was total sampling with 38 respondents. The measuring instrument in this study used a questionnaire sheet. Data analysis was performed using the chi-square test. The result of this study is that the p-value of 0.000 is smaller than a significant value of 0.05, so there is a relationship between psychological stress and milk production in breastfeeding mothers after childbirth at the Wulandari Clinic, Medan in 2021.